PROGRAM PENGUATAN KEPALA SEKOLAH OLEH PENGAWAS DALAM MENINGKATKAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DI SMPN 04 SENGAH TEMILA - Hendri Hendri; Wahyudi Wahyudi; Syukri Syukri (Universitas Tanjungpura, 2020)
AbstractThe problem studied was the Principal Strengthening Program by the Supervisor is an activity carried out individually to improve the principal's performance. The research method used by researchers is a qualitative approach. Data was collected through interviews, observations, documentation and analyzed through data reduction, data presentation, conclusions or verification. The results of the study showed that from 16 indicators of school principal's competency management in SMPN 4 Sengah Temila, only 11 indicators were successfully implemented, namely: 1) Change and development, 2) Managing Teachers and staff 3) Managing schools, 4) Managing SARPRAS, 5) Managing Students in PPDB, 6) Manage Administration, 7) Manage special service units, 8) Manage information systems, 9) Manage Finances, 10) Manage school relationships with the community, and 11) Monitor, evaluate and report. 3 Indicators that are not yet understood, namely: 1) Arranging plans, 2) Leading schools in the utilization of school resources, and 3) Developing school organizations. Whereas 2 Indicators which were not implemented were 1) Creating school culture and climate, 2) Utilizing information technology advancements. The implication was that the 16 principals' managerial competencies determine the performance of the principal if implemented properly so that the desired work results are achieved. Keywords: Strengthening Principals By Supervisors.